Bacterial cellulose hydrogel produced by Gluconacetobacter hansenii using sugarcane molasses as medium: Physicochemical characterization for wound healing applications - Carvalho, Rafaela Siqueira Ferraz de; Mahnke, Layla Carvalho; Palácio, Sarah Brandão; Barbosa, Willams Teles; Hodel, Katharine Valeria Saraiva; Barbosa, Josiane Dantas Viana; Melo, Francisco de Assis Dutra; Chorilli, Marlus [UNESP]; Meneguin, Andreia Bagliotti [UNESP]; Pinto, Flavia Cristina Morone; Morais, Marcos Antônio de; Aguiar, José Lamartine de Andrade (Elsevier, 2025)
Biopolymers, such as Bacterial Cellulose (BC) have attracted commercial interest especially due to their physicochemical properties and the potential applications. This work presents the BC physicochemical characterization obtained by Gluconacetobacter hansenii in a sugarcane molasses medium. The structural and morphological characteristics of BC evidenced a typical cellulose structure reported in previous research where BC was obtained by different strains and fermentation conditions. The properties of BC, considering the ideal parameters for applications, were analyzed using the following methods: tensile tests; water activity; swelling profile and moisture content; water vapor permeability and in vitro degradation analysis. The BC film was characterized by a high porosity (85.5 %); high tensile strength (46.2 MPa); low water activity (0.31 aw); high swelling index (59.5 %) and water swell ability (190 %). These properties make BC an excellent candidate for biomedical application, especially for dressing production, re-epithelialization and skin regeneration. The data obtained in this study is intended to support the use of sugarcane molasses, a pure substrate from a renewable and inexpensive source, as a potential substrate for the synthesis of BC with properties for application in medicine.
Keywords: Biopolymer; DNA sequencing; Exopolysaccharide; Gluconacetobacter hansenii; Polysaccharide; Wound dressing